Exploring techno-economic landscapes of abatement options for hard-to-electrify sectors - Clara Bachorz; Philipp C. Verpoort; Gunnar Luderer; Falko Ueckerdt (Nature Communications)
Abstract Approximately 20% of global CO2 emissions originate from sectors often labeled as hard-to-abate, which are challenging or impossible to electrify. Alternative abatement options are necessary for these sectors but face critical bottlenecks, particularly concerning the availability and cost of low-emission hydrogen, carbon capture and storage, and non-fossil CO2 for synthetic fuels or carbon-dioxide removal. In this study, we conduct a broad techno-economic analysis, mapping abatement options and hard-to-electrify sectors while addressing associated technological uncertainties. Our findings reveal a diverse mitigation landscape that can be categorized into three tiers, based on the abatement cost and technologies required. By requiring long-term climate neutrality through simple conditions, the mitigation landscape narrows substantially, with single options dominating each sector. This clarity justifies targeted political support for sector-specific abatement options, increasing investment security for transforming hard-to-electrify sectors.